Chiral analysis of β-alanyl-d,l-tyrosine and its derivatives and estimation of binding constants of their complexes with 2-hydroxypropyl-β-cyclodextrin by capillary electrophoresis - Sázelová, Petra; Šolínová, Veronika; Schimperková, Tereza; Jiráček, Jiří; Kašička, Václav (Journal of separation science, 2022)
Chiral CE methods were developed for the elucidation of l- or d-configuration of tyrosine residue in antimicrobial dipeptide β-alanyl-tyrosine (β-Ala-Tyr) isolated from the hemolymph of larvae of fleshfly Neobellieria bullata and for the evaluation of enantiopurity of its synthetic isomers (β-Ala-d-Tyr and β-Ala-l-Tyr), and enantiomers of their amidated and acetylated derivatives, β-Ala-d,l-Tyr-NH2 and N-Ac-β-Ala-d,l-Tyr, respectively. Baseline separations were achieved for all three pairs of enantiomers: (i) for β-Ala-d,l-Tyr in acidic background electrolyte composed of 32/50 mM tris(hydroxymethyl)aminomethane/H3 PO4 , pH 2.5, and 20 mg/mL 2-hydroxypropyl-β-cyclodextrin as chiral selector; (ii) for β-Ala-d,l-Tyr-NH2 enantiomers in acidic background electrolyte consisting of 48/50 mM tris(hydroxymethyl)aminomethane/H3 PO4 , pH 3.5, and 30 mg/mL 2-hydroxypropyl-β-cyclodextrin; and (iii) for enantiomers of N-Ac-β-Ala-d,l-Tyr in alkaline background electrolyte composed of 50/49 mM Na2 B4 O7 /NaOH, pH 10.5, and 60 mg/mL 2-hydroxypropyl-β-cyclodextrin. From CE analyses of mixed samples of isolated β-Ala-Tyr and synthetic standards β-Ala-l-Tyr and β-Ala-d-Tyr, it turned out that isolated β-Ala-Tyr was pure l-enantiomer. In addition, the average apparent binding constants, Kb , and average actual ionic mobilities of the complexes of β-Ala-d,l-Tyr and its above derivatives with 2-hydroxypropyl-β-cyclodextrin were determined. These complexes were weak, with Kb values ranging from 11.2 to 79.1 L/mol. Their cationic mobilities were equal to (5.6-9.2) × 10-9 m2 /V/s, and anionic mobilities to (-1.3-1.6) × 10-9 m2 /V/s.
Keywords: beta-Cyclodextrins; stereoizomerie; Cyclodextrins; Binding constant; hydroxypropyl beta cyklodextrin; Electrolytes; 2-hydroxypropyl-β-cyclodextrin; Tyrosine; Electrophoresis, Capillary; enantioseparation; β-alanyl-tyrosine; Stereoisomerism; tromethamin; elektroforéza kapilární; beta-cyklodextriny; 2-Hydroxypropyl-beta-cyclodextrin; elektrolyty; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; capillary electrophoresis; tyrosin; cyklodextriny; chiral separation; Tromethamine